Forensic interlaboratory evaluation of the ForFLUID kit for vaginal fluids identification - Giampaoli, Saverio; Alessandrini, Federica; Berti, Andrea; Ripani, Luigi; Choi, Ajin; Crab, Roselien; De Vittori, Elisabetta; Egyed, Balazs; Haas, Cordula; Lee, Hwan Young; Korabecná, Marie; Noel, Fabrice; et al. (Journal of forensic and legal medicine, 2014)
Identification of vaginal fluids is an important step in the process of sexual assaults confirmation. Advances in both microbiology and molecular biology defined technical approaches allowing the discrimination of body fluids. These protocols are based on the identification of specific bacterial communities by microfloraDNA (mfDNA) amplification. A multiplex real time-PCR assay (ForFLUID kit) has been developed for identifying biological fluids and for discrimination among vaginal, oral and fecal samples. In order to test its efficacy and reliability of the assay in the identification of vaginal fluids, an interlaboratory evaluation has been performed on homogeneous vaginal swabs. All the involved laboratories were able to correctly recognize all the vaginal swabs, and no false positives were identified when the assay was applied on non-vaginal samples. The assay represents an useful molecular tool that can be easily adopted by forensic geneticists involved in vaginal fluid identification.
Keywords: dospělí; Female; Multiplex PCR; Streptococcus; Lactobacillus; Adult; ženské pohlaví; DNA bakterií; Vagina; DNA, Bacterial; lidé; Staphylococcus; cervikální hlen; Cervix Mucus; Laboratories; Interlaboratory evaluation; Forensic Medicine; Forensic; laboratoře; multiplexová polymerázová řetězová reakce; Multiplex Polymerase Chain Reaction; kvantitativní polymerázová řetězová reakce; Bacteria; Vaginal fluids; Enterococcus faecalis; soudní lékařství; mfDNA; vagina; Real-Time Polymerase Chain Reaction; Humans